A Trithia-Bridged N-Heterotriangulene: The Hitherto Missing Electron Donor - Borstelmann, Jan; Gensch, Viktoria; Fehn, Dominik; Miehlich, Matthias; Hampel, Frank; Rominger, Frank; Meyer, Karsten; Kivala, Milan (Angewandte Chemie International Edition, 2024)
The very first representative of trithia-bridged N-heterotriangulene, a triphenylamine with sulfur atoms bridging the ortho-positions, was synthesized by a sequence of regioselective sulfenylation with phthalimidesulfenyl chloride followed by Lewis acid-catalyzed electrophilic cyclization. X-ray crystallography revealed a saddle-shaped geometry of the polycyclic scaffold. UV/Vis absorption spectroscopy and cyclic voltammetry were used to characterize the optoelectronic properties. The title compound is a particularly strong electron donor forming a perfectly stable radical cation, which was analyzed by electron paramagnetic resonance spectroscopy and X-ray crystallography. The electron donor properties were further highlighted by the formation of crystalline donor-acceptor complexes with strong cyano-based acceptors.
CRIS-Team Scopus Importer:2025-02-04
Keywords: electrochemistry; electron donor; N-heterotriangulene; radical cation; sulfur

Fully Bridged Triphenylamines Comprising Five- and Seven-Membered Rings - Michalsky, Ina; Gensch, Viktoria; Walla, Christian; Hoffmann, Marvin; Rominger, Frank; Oeser, Thomas; Tegeder, Petra; Dreuw, Andreas; Kivala, Milan (Chemistry - A European Journal, 2022)
A family of fully bridged triphenylamines with embedded 5- and 7-membered rings is presented. The compounds are potent electron donors capable to undergo donor/acceptor interactions with strong cyano-based acceptors both in the solid state and solution. These interactions were evaluated by IR and UV/vis spectroscopy as well as X-ray crystallography. The vinylene-bridged compound was oxidized to the corresponding 1,2-diketone which readily underwent acid-catalyzed condensation with selected 1,2-phenylenediamines. The resulting π-extended quinoxaline derivatives represent valuable building blocks for the development of functional chromophores upon appropriate functionalization.
CRIS-Team Scopus Importer:2022-05-20
Keywords: bridged triarylamines; charge transfer; co-crystallization; electron donor; N-heterocycle